RNA‐Seq analysis of the guppy immune response against Gyrodactylus bullatarudis infection. (5th September 2020) - Konczal, Mateusz; Ellison, Amy R.; Phillips, Karl P.; Radwan, Jacek; Mohammed, Ryan S.; Cable, Joanne; Chadzinska, Magdalena
Abstract: Gyrodactylids are ubiquitous ectoparasites of teleost fish, but our understanding of the host immune response against them is fragmentary. Here, we used RNA‐Seq to investigate genes involved in the primary response to infection with Gyrodactylus bullatarudis on the skin of guppies, Poecilia reticulata, an important evolutionary model, but also one of the most common fish in the global ornamental trade. Analysis of differentially expressed genes identified several immune‐related categories, including IL‐17 signalling pathway and Th17 cell differentiation, cytokine‐cytokine receptor interaction, chemokine signalling pathway, NOD‐like receptor signalling pathway, natural killer cell‐mediated cytotoxicity and pathways involved in antigen recognition, processing and presentation. Components of both the innate and the adaptive immune responses play a role in response to gyrodactylid infection. Genes involved in IL‐17/Th17 response were particularly enriched among differentially expressed genes, suggesting a significant role for this pathway in fish responses to ectoparasites. Our results revealed a sizable list of genes potentially involved in the teleost‐gyrodactylid immune response.